2001
DOI: 10.1046/j.1365-2265.2001.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo secretory potential and the effect of combination therapy with octreotide and cabergoline in patients with clinically non‐functioning pituitary adenomas

Abstract: The secretory capacity, in vivo, of clinically non-functioning pituitary adenomas may possibly predict tumour volume reduction during intensive medical therapy. Ten patients (mean (range) 53 years (26-73)) with clinically non-functioning macroadenomas, > or = 10 mm were studied. The secretory capacity of the adenomas was examined using basal, NaCl and TRH-stimulated LH, FSH and alpha-subunit levels. The effect on tumour volume of 6 months' therapy with the combination of a somatostatin analogue, octreotide 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 30 publications
0
24
0
5
Order By: Relevance
“…These data would indicate a stimulatory role for SSTR5 in NFA cell proliferation, suggesting that the use of compounds selectively interacting with SSTR5 in NFA medical therapy might be counterproductive. In addition, this effect might account for the lack of volume reduction (Colao et al 2000, Andersen et al 2001 or the increase in tumor volume (Gasperi et al 1993) observed in NFA patients treated with octreotide or lanreotide, which mainly interacts with SSTR2 and SSTR5. However, this does not seem to be a general mechanism in pituitary adenomas, because previous evidence from somatotroph and corticotroph pituitary tumors suggests that the additional activation of SSTR5 might be responsible for the enhanced efficacy of SRIF analogs in reducing both secretion and cell proliferation (Shimon et al 1997, Hofland et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…These data would indicate a stimulatory role for SSTR5 in NFA cell proliferation, suggesting that the use of compounds selectively interacting with SSTR5 in NFA medical therapy might be counterproductive. In addition, this effect might account for the lack of volume reduction (Colao et al 2000, Andersen et al 2001 or the increase in tumor volume (Gasperi et al 1993) observed in NFA patients treated with octreotide or lanreotide, which mainly interacts with SSTR2 and SSTR5. However, this does not seem to be a general mechanism in pituitary adenomas, because previous evidence from somatotroph and corticotroph pituitary tumors suggests that the additional activation of SSTR5 might be responsible for the enhanced efficacy of SRIF analogs in reducing both secretion and cell proliferation (Shimon et al 1997, Hofland et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Page 6, paragraph 1, line 14: the paragraph "This effect might explain the lack of efficacy of medical treatment by means of octreotide or Lan, compounds mainly interacting with SSTR2 and less with SSTR5, in some NFA (Oppizzi et al 1998, Andersen et al 2001, Colao et al 2000, Gasperi et al 1993. Moreover, our findings might provide a possible explanation for the increase in tumor volume rarely observed during such therapy (Andersen et al 2001). These results suggest that indication for medical therapy with octreotide or Lan in NFA patients with SSTR5 expressing tumors should be critically discussed until clinical evidence for beneficial effects has clearly been demonstrated."…”
Section: Physiol 94 205-210mentioning
confidence: 99%
“…On the contrary, our data show that the SSTR2 selective agonist did not influence NFA cell viability, which was promoted by the SSTR5 selective agonist. This effect might explain the lack of efficacy of medical treatment by means of octreotide or Lan, compounds mainly interacting with SSTR2 and less with SSTR5, in some NFA (Oppizzi et al 1998, Andersen et al 2001, Colao et al 2000, Gasperi et al 1993. Moreover, our findings might provide a possible …”
mentioning
confidence: 99%
“…As already mentioned, a functional interaction between D 2 and sst 5 receptors has recently been reported (15), supporting a potential benefit from combined use of these two categories of compounds. In a recent study, the effect of combination therapy with octreotide and cabergoline was investigated in ten patients with NFA (55). Tumour shrinkage O10% has been reported in six out of ten patients.…”
Section: Non-functioning Pituitary Adenomasmentioning
confidence: 99%